Bio-inspired cross-linking with borate for enhancing gas-barrier properties of poly(vinyl alcohol)/graphene oxide composite films. (February 2015) - Lai, Cheng-Lee; Chen, Jung-Tsai; Fu, Ywu-Jang; Liu, Wei-Ren; Zhong, Yueh-Ru; Huang, Shu-Hsien; Hung, Wei-Song; Lue, Shingjiang Jessie; Hu, Chien-Chieh; Lee, Kueir-Rarn
Abstract: The demand for flexible and transparent barrier films in industries has been increasing. Learning from nature, borate ions were used to cross-link poly(vinyl alcohol) (PVA) and graphene oxide (GO) to produce flexible, transparent high-barrier composite films with a bio-inspired structure. PVA/GO films with only 0.1 wt% GO and 1 wt% cross-linker exhibited an O2 transmission rate <0.005 cc m −2 day −1, an O2 permeability <5.0 × 10 −20 cm 3 cm cm −2 Pa −1 s −1, and a transmittance at 550 nm >85%; thus, they can be used for flexible electronics. Fourier transform infrared spectrometry and X-ray photoelectron spectroscopy indicated that the outstanding barrier properties are attributed to the formation of chemical cross-linking involving borate ions, GO sheets, and PVA, similar to the borate cross-links in high-order plants. Comparing our experimental data with the Cussler model, we found that the effective aspect ratio was significantly increased after cross-linking, suggesting that cross-linking networks connected GO with each other to form ultra-large impermeable regions. A feasible green technique, with potential for commercial production of barrier films for flexible electronics was presented.